Properties and Structure of RO‐R2O‐Na2O‐Al2O3‐P2O5 Glasses - Budi, Agus Setyo; Herawan, Safarudin Gazali; Ahmad, Asmala; Sunaryo, - (American Institute of Physics, 2007)
The properties and structural features of RO-R20-Na 20-Al203-P205 (R= Mg, Ca, Ba and RO= Li) glasses in the system have been investigated. The properties of those glasses seem to depend on the field strength of the alkali or alkali-earth ions in glasses as in silicate glasses. Infrared (IR) spectroscopy indicates that the glass network is dominated by bridging P-tetrahedral present in glasses with O/P ~ 3.0. The variation in physical properties of the glasses seem to be closely related to the variation in structure of the glasses and could be explained by simple mechanism such as field strength and differences in mass.